Crystallographic analyses illustrate significant plasticity and efficient recoding of meganuclease target specificity - Werther,R; Hallinan,JP; Lambert,AR; Havens,K; Pogson,M; Jarjour,J; Galizi,R; Windbichler,N; Crisanti,A; Nolan,T; Stoddard,BL (Nucleic Acids Research, 2017)
The retargeting of protein–DNA specificity, outsideof extremely modular DNA binding proteins suchas TAL effectors, has generally proved to be quitechallenging. Here, we describe structural analysesof five different extensively retargeted variants of asingle homing endonuclease, that have been shownto function efficiently in ex vivo and in vivo applications.The redesigned proteins harbor mutationsat up to 53 residues (18%) of their amino acid sequence,primarily distributed across the DNA bindingsurface, making them among the most signifi-cantly reengineered ligand-binding proteins to date.Specificity is derived from the combined contributionsof DNA-contacting residues and of neighboringresidues that influence local structural organization.Changes in specificity are facilitated by theability of all those residues to readily exchange bothform and function. The fidelity of recognition is notprecisely correlated with the fraction or total numberof residues in the protein–DNA interface that areactually involved in DNA contacts, including directionalhydrogen bonds. The plasticity of the DNArecognitionsurface of this protein, which allows substantialretargeting of recognition specificity withoutrequiring significant alteration of the surroundingprotein architecture, reflects the ability of the correspondinggenetic elements to maintain mobility andpersistence in the face of genetic drift within potentialhost target sites.